Small Abundant DNA Binding Proteins from the Thermoacidophilic Archaeon Sulfolobus shibatae Constrain Negative DNA Supercoils - Mai, Viet Q. (American Society for Microbiology, 1998)
Major DNA binding proteins, designated Ssh7, were purified from the thermoacidophilic archaeon Sulfolobus shibatae. The Ssh7 proteins have an apparent molecular mass of 6.5 kDa and are similar to the 7-kDa DNA binding proteins from Sulfolobus acidocaldarius and Sulfolobus solfataricus in N-terminal amino acid sequence. The proteins constitute about 4.8% of the cellular protein. Upon binding to DNA, the Ssh7 proteins constrain negative supercoils. At the tested Ssh7/DNA mass ratios (0 to 1.65), one negative supercoil was taken up by approximately 20 Ssh7 molecules. Our results, together with the observation that the viral DNA isolated from S. shibatae is relaxed, suggest that regions of free DNA in the S. shibatae genome, if present, are highly positively supercoiled.